Correlation between posteromedial or posterolateral displacement and cubitus varus deformity in supracondylar humerus fractures in children - (:unkn) unknown (My University, 2008)
Purpose Cubitus varus deformity is one of the most common complications after displaced supracondylar humeral fractures in children. The purpose of this study was to evaluate the relationship between the fracture displacement and cubitus varus deformity in displaced supracondylar humerus fractures. Methods Seventeen patients (11 males/6 females; mean age 7 years) with cubitus varus deformities occurring after Gartland type III posteromedial or posterolateral displaced supracondylar humerus fractures were evaluated with clinical and serial radiographic examinations. All patients had been treated surgically by open reduction through a medial approach and percutaneous cross-pinning. All fractures were reduced anatomically. Ten of the patients were operated within the first 24 h. The time interval between the initial injury and the surgical procedure for the remaining seven patients was 5.3 days on average (range 2–10 days). The carrying angle and range of motion of the elbow were measured throughout the follow-up period. The mean follow-up time was 3.7 years (range 2–12 years). Results Five patients with type III-B fractures had a mean carrying angle loss of 8.8° (range 6–10°), whereas for the remaining 12 type III-A patients the mean loss was 15° (range 6–29°) ( P = 0.019). None of the patients in this study demonstrated limited elbow motion. According to the Flynn criteria, the results were good in five type III-B patients. There was no statistically significant relationship between the loss of carrying angle and the delay before the surgical procedure ( P = 0.615 in type III-A, P = 0.096 in type III-B). Conclusions The carrying angle loss was more significant in type III-A fractures compared with type III-B in this series. These results suggest that although anatomic reduction has been achieved by surgical treatment without loss of reduction, there is still a risk for cubitus varus deformity for type III-A fractures due to the initial compression of the medial column or, in other words, physeal injury.